Iron dissolution and speciation in atmospheric mineral dust: Metal-metal synergistic and antagonistic effects. (August 2018) - Hettiarachchi, Eshani; Reynolds, Richard L.; Goldstein, Harland L.; Moskowitz, Bruce; Rubasinghege, Gayan
Abstract: Under acidic atmospheric conditions, iron leached from atmospheric mineral dust may influence the distribution of bioavailable iron at a global scale. However, the effects of non-Fe-containing minerals on iron dissolution remain unknown. This work describes metal-metal synergistic and antagonistic effects on iron dissolution that go beyond aggregation and ionic strength effects in mineral dust mixtures. In this study, we investigated iron mobilization by proton-promoted dissolution in natural mineral dust samples from the Kalahari Desert (SZ1) and Australian Red Dawn event (RO), along with one iron oxide proxy, hematite. The total iron dissolution in natural dust samples highly corresponds with the respective amount of Ti, rather than their particle sizes or Fe contents. The dust sample with high Ti content, SZ1, also showed a higher fraction of dissolved Fe(II), under dark conditions. These observations are in good agreement with the dissolution data for hematite artificially mixed with metal oxides. Total iron dissolution in hematite, mixed with TiO2, is 1.5- and 2-fold higher compared to that of just hematite under dark and light conditions, respectively. However, dissolution of hematite is suppressed when mixed with Al2 O3 and CaO. Under dark conditions, furthermore, dissolved Fe(II) fraction is enhanced for hematite when mixed with TiO2 compared to that of other mixtures or hematite alone. Yet, dissolved Fe(II) is lower in hematite mixed with TiO2 under light conditions compared to that of hematite alone, suggesting photo-oxidation of Fe(II) by reactive oxygen species, such as OH radicals. Graphical abstract: Image 1 Highlights: Mineral dusts with high %Ti show enhanced total iron dissolution. When hematite is mixed with TiO2, iron dissolution increases. Photochemical properties of TiO2 further enhances iron dissolution in mineral dust. CaO or Al2 O3 diminishes iron solubility due to their inherent basic properties. The observed differences in iron dissolution go beyond ionic strength effects.